Intravitreal Ranibizumab Injection for the Treatment of Retinopathy of Prematurity - Aldebasi, Tariq (Med Princ Pract, 2019)
OBJECTIVES: To evaluate the efficacy of a single injection of 0.3 mg intravitreal ranibizumab for the treatment of retinopathy of prematurity (ROP). METHODS: We conducted this retrospective case series study at King Abdul Aziz Medical City, Riyadh, Saudi Arabia. Seventy-four eyes of 37 preterm infants with ROP stage III with plus disease in zone I, posterior zone II, and aggressive posterior ROP received a single injection of 0.3 mg intravitreal ranibizumab. The favorable outcome measure was complete regression of the disease with normal vascularization of the retina of those infants. RESULTS: The gestational age of the 37 included cases was in the range of 23–28 weeks and their body weight at birth was between 510 and 1,235 g except for one case with 2,550 g under oxygen therapy <7days with severe hypoglycemia. All eyes showed a favorable response in terms of regression of plus disease from the first day after treatment, followed by regression of stage III retinopathy. All patients developed complete vascularization over variable periods of time. CONCLUSION: One injection of 0.3 mg intravitreal ranibizumab is effective in treating ROP stage III mainly in zones I and II.